Cerkiew w życiu społeczno-politycznym Ukrainy w latach 1991–2010 - Jędraszczyk, Katarzyna (Studia Europaea Gnesnensia, 2011)
There is no single dominant religion with which most of the populace would iden-tify. The churches are largely regional in nature. The Ukrainian Orthodox Church — Kyiv Patriarchate, and the Ukrainian Orthodox Church — Moscow Patriarchate, have become, for the politicians as well as for the people, the symbols of two “Ukrainian projects”. Their simultaneous functioning for almost twenty years, have become inter-twined in the process of formation of a political nation, which subsumes all identities of the post-Soviet territory of Ukraine. The fact that certain politicians equate the issue of belonging to a particular denomination with the problem of loyalty to one’s own state, obstructs the dialogue among orthodox churches and does not benefit social consolidation.